1985
DOI: 10.1530/acta.0.1090369
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative aspects of the effects of insulin, epidermal growth factor and dexamethasone on DNA synthesis in cultured adult rat hepatocytes

Abstract: Abstract. Epidermal growth factor (EGF) and insulin in combination have previously been shown to initiate S-phase in primary cultures of adult rat hepatocytes. We here describe the detailed time course and dosedependency of the effects of EGF and insulin on DNA synthesis in cultured hepatocytes. The DNA synthesis was assessed either biochemically or autoradiographically with a fairly good correlation between the two methods. DNA synthesis started 24–30 h after plating of the cells and peaked at approximately 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…This demonstrates that high-dose dexamethasone (10 −8 M) inhibits the HGF-induced hepatocyte DNA synthesis and proliferation downstream of ERK2. The present results support the notion that dexamethasone (10 −8 M) suppresses HGF-induced DNA synthesis and proliferation (i.e., cell cycle progression) at the nuclear level (27). We also found that dexamethasone dose-dependently inhibited EGF-and PDGF-induced hepatocyte DNA synthesis and proliferation (accepted for publication).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This demonstrates that high-dose dexamethasone (10 −8 M) inhibits the HGF-induced hepatocyte DNA synthesis and proliferation downstream of ERK2. The present results support the notion that dexamethasone (10 −8 M) suppresses HGF-induced DNA synthesis and proliferation (i.e., cell cycle progression) at the nuclear level (27). We also found that dexamethasone dose-dependently inhibited EGF-and PDGF-induced hepatocyte DNA synthesis and proliferation (accepted for publication).…”
Section: Discussionsupporting
confidence: 90%
“…Glucocorticoids such as dexamethasone and hydrocortisone have been reported to affect cell attachment and viability, but not proliferation (5,15). However, the concentrations (about 10 −9 -10 −5 M) and timing of glucocorticoid addition to cultures has varied among investigators (5,6,27,28). Especially, these doses are higher compared with our experimental condition.…”
Section: Discussionmentioning
confidence: 72%
“…To determine whether dexamethasone altered the ErbB expression profile, we cultured cells in the presence of 10 Ϫ8 or 10 Ϫ6 M dexamethasone for 72 h. We cultured the cells in both insulin (100 nM) and a submitogenic dose of TGF-␣ (0.1 nM) to enhance cell viability. Insulin was also added because it is required to preserve maximal TGF-␣ responsiveness of hepatocytes after 24 h of culture (30). Lysates were immunoblotted for the four ErbB proteins at 24, 48, and 72 h. Confirming our previous experience, no ErbB4 was detected.…”
Section: Resultsmentioning
confidence: 55%
“…Given the temporal changes of ErbB protein expression in vitro, we further speculated that the overall influence of dexamethasone on the hepatocellular response to EGF-type ligands depends on the time of growth factor addition. Our analysis of prior work suggested that the stimulatory effects of dexamethasone occurred when EGF and dexamethasone were added simultaneously at the beginning of the culture period (30). In contrast, the inhibitory action occurred when isolated hepatocytes were plated in a high concentration of dexamethasone for at least 24 h before EGF exposure (35).…”
mentioning
confidence: 86%
See 1 more Smart Citation